Effectiveness of the “Heart” Animated Educational Video on Medication Adherence Among Hypertensive Patients - Kartika Indarti Pinanggih; Sri Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a common non-communicable condition with inadequate drug adherence. Noncompliance with antihypertensive treatment can lead to stroke, heart failure, and kidney problems. Health education through the HEART (Hypertension Education and Resource Toolkit) animated movie being tested to improve medication adherence in hypertension patients at Sebelas Maret University Hospital (UNS) Solo. The study was quasi-experimental with a single group pretest–posttest. Purposive sampling yielded 94 individuals. The Wilcoxon Signed Rank test was used to analyze the results before and after the intervention using the MMAS-8 questionnaire with Cronbach's Alpha validity test. The Morisky Medication Adherence Scale 8 (MMAS-8) was 0.83, indicating high internal consistency. Reliability was tested using the test-retest reliability method with a Cronbach's Alpha coefficient of 0.898. Education significantly increased adherence (p = 0.001), with 96.8% of patients non-adherent before the intervention and 91.5% moderately and 3.2% totally adherent afterward. These findings demonstrate that audiovisual educational media improves patient comprehension and adherence. In conclusion, UNS Solo Hospital hypertension patients' medication adherence has improved using the HEART animated movie.